2013
DOI: 10.1002/zaac.201200554
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Nanoscopic Magnesium Hydroxide ­Fluorides Studied by Natural Abundance 25Mg Solid State NMR Spectroscopy

Abstract: Along with X-ray diffraction measurements, 25 Mg solid state NMR experiments were performed in natural abundance at 9.4 T on crystalline and mechanically milled samples of MgO, Mg(OH) 2 , MgF 2 , and magnesium hydroxide fluorides Mg(OH) x F 2-x prepared on mechanochemical and sol-gel syntheses routes. In addition to single pulse and spin-echo sequences, both static 1 H-25 Mg CP and 19 F-25 Mg CP measurements allowed the registration of 25 Mg spectra in attractive 694 short measurement times. Although an assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In the current study, multinuclear ( 1 H, 13 C, 25 Mg) solid-state NMR is reported for Mg(OAc) 2 · 4H 2 O, Mg(OAc) 2 · H 2 O and Mg(OAc) 2 with an emphasis on 25 Mg. The crystal structures based on single crystal work has been reported for these phases.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…In the current study, multinuclear ( 1 H, 13 C, 25 Mg) solid-state NMR is reported for Mg(OAc) 2 · 4H 2 O, Mg(OAc) 2 · H 2 O and Mg(OAc) 2 with an emphasis on 25 Mg. The crystal structures based on single crystal work has been reported for these phases.…”
Section: Introductionmentioning
confidence: 91%
“…1 H MAS NMR spectra were recorded using a depth pulse sequence. 13 C and 1 H MAS NMR spectra (10 kHz MAS, 16.4 T) were run before and after the 25 Mg experiments and showed no phase change as a result of spinning the samples for lengthy periods, indicating that the water remains bound to the magnesium. 25 Mg solid-state NMR spectra were also obtained at 20.0 T on a Bruker Avance 850 MHz spectrometer operating at a Larmor frequency of 52.0 MHz.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sol-gel synthesized magnesium fluoride consists of agglomerated nanocrystals in the rutile structure, the surface properties of which can be controlled through changes in the synthetic conditions, e.g. temperature and partial pressure of hydrogen fluoride and water [6][7][8][9]. By now well established, this method has opened new possibilities for the production of high-surface, thus highly active, nanomaterial with tunable properties for heterogeneous catalysis applications.…”
Section: Introductionmentioning
confidence: 99%